The trend and direction of issues regarding the coverage of the Election Bill on Kompas.com - Fauzan; Zulfikar, Fikri (Jurnal Mercusuar, 2022)
The main problem to be addressed in this study is "How is the Issue Trend and Issue Direction regarding the Election Bill (RUU Pemilu) covered in Kompas.com?" The issue trend and issue direction are related to public opinion and the process of forming public opinion. Therefore, the relevant theory used to explain this is the causal funnel. The method used to answer this question is Environmental Monitoring Program Audit, the early warning phase. The application of this method borrows the procedures of content analysis. The difference lies in the determination of the sample. The research findings on the issue of the Election Bill on Kompas.com in three periods (Period I = 32.6%, Period II = 24.2%, and Period III = 28.7%) were the same, which is highlighting the issue trend of the Presidential Threshold. The Issue Trend on the Presidential Threshold is due to Kompas.com editorial policy emphasizing the implementation of the Presidential Election. The research findings on the issue direction of the Election Bill on Kompas.com in three periods (Period I = 47.8%, Period II = 40.9%, and Period III = 44.8%) are neutral. Thus, the trend of the issue direction of Election Bill coverage is neutral. The coverage of the Election Bill on Kompas.com has positive issue direction (Period I = 34.8%, Period II = 40.3%, and Period III = 28.7%) and negative issue direction (Period I = 17.4%, Period II = 18.8%, and Period III = 26.4%), which is not unrelated to editorial policy that takes sources from within and outside the palace. The tendency of the neutral issue direction trend is due to editorial policy that prioritizes public agenda. This choice has implications for the balanced selection of sources from both the palace and outside the palace.